PENDIDIKAN ADVERSITY QUOTIENT DALAM KONSEP ISLAM - Muh. Haris Zubaidillah (Program Studi PAI STAI Al Falah Banjarbaru, 2018)
Humans are principally born to have the nature of the climbing. This ascent means its move to achieve the goals of life into the future. Then Adversity Quotient is part of determining someone's success to reach the ascent of climbing. Instinctively, the process of climbing will be faced with various obstacles, challenges, and difficulties. All of that cannot only be solved by capitalizing on intellectual intelligence but also with the help of emotional, spiritual intelligence and Adversity Quotient. In this article, the author wants to explore Adversity Quotient Education in the concept of Islam. Adversity Quotient Education in Islamic concepts includes patient education, optimistic education, and unyielding, high-minded education and jihad education. Patient education is in line with the control dimension of Adversity Quotient, education is optimistic and unyielding in line with the dimensions of ownership in Adversity Quotient, education with a great spirit is aligned with the reach dimensions of Adversity Quotient and jihad education in line with the endurance dimension of Adversity Quotient. These educational values are indispensable in Islamic education, in order to produce generations of Muslims who love struggle, never give up with all obstacles, dare to face challenges, are immune to difficulties and enthusiasm in living life, especially in the world of education. Keywords: Adversity Quotient, Islam, Education.